Strategies for improved isopropanol–butanol production by a Clostridium strain from glucose and hemicellulose through consolidated bioprocessing - Xin, Fengxue; Chen, Tianpeng; Jiang, Yujiang; Dong, Weiliang; Zhang, Wenming; Zhang, Min; Wu, Hao; Ma, Jiangfeng; Jiang, Min (Biotechnology for biofuels, 2017)
High cost of traditional substrates and formation of by-products (such as acetone and ethanol) in acetone-butanol-ethanol (ABE) fermentation hindered the large-scale production of biobutanol. Here, we comprehensively characterized a newly isolated solventogenic and xylanolytic species, which could produce butanol at a high ratio with elimination of ethanol and conversion of acetone to more value-added product, isopropanol. Ultimately, direct butanol production from hemicellulose was achieved with efficient expression of indigenous xylanase by the novel strain via consolidated bioprocessing. A novel wild-type sp. strain NJP7 was isolated and characterized in this study, which was capable of fermenting monosaccharides, e.g., glucose into butanol via a fermentative acetone-isopropanol-butanol pathway. With enhancement of buffering capacity and alcohol dehydrogenase activities, butanol and isopropanol titer by sp. strain NJP7 was improved to 12.21 and 1.92 g/L, respectively, and solvent productivity could be enhanced to 0.44 g/L/h. Furthermore, with in situ extraction with biodiesel, the amount of butanol and isopropanol was finally improved to 25.58 and 5.25 g/L in the fed-batch mode. Meanwhile, sp. strain NJP7 shows capability of direct isopropanol-butanol production from hemicelluloses with expression of indigenous xylanase. 2.06 g/L of butanol and 0.54 g/L of isopropanol were finally achieved through the temperature-shift simultaneous saccharification and fermentation, representing the highest butanol production directly from hemicellulose. The co-production of isopropanol with butanol by the newly isolated sp. strain NJP7 would add on the economical values for butanol fermentation. Furthermore, the high isopropanol-butanol production with in situ extraction would also greatly enhance the economic feasibility for fermentative production of butanol-isopropanol in large scale. Meanwhile, its direct production of butanol-isopropanol from polysaccharides, hemicellulose through secretion of indigenous thermostable xylanase, shows great potential using lignocellulosic wastes for biofuel production.